Quo vadis Common Agricultural Policy of the European Union? - Stępień Sebastian; Czyżewski Andrzej (Management, 2019)
The agricultural policy of the European Union - Common Agricultural Policy (CAP) - was introduced in the 1960s as the first EU policy. Over the next decades it constituted the largest share in the expenditure of the EU budget. Today, although cohesion policy has replaced it in the first place, it is still being prioritized by the countries of the Community. Observation of the next financial perspectives, however, allows to conclude that the nature of the CAP is changing, which is a manifestation of the evolution of views on the role of the food sector in the economic development of the European Union. The aim of the study is to indicate the directions of reforms of the Common Agricultural Policy during its sixty-year functioning, the reasons for these changes and the consequences they have had for the agricultural sector in EU countries. These outcomes were supplemented by outlining the perspectives for the development of the EU agricultural policy in the coming years. The authors focused on the basic instruments of the CAP including income-generating, environmental and rural development-related. On the basis of the analysis of objectives and instruments of the CAP, it was stated that it departed from traditional market support to create more sophisticated intervention related to the changing macroeconomic conditions and expectations of the society. The paper is a review, with elements of meta-analysis, deduction and inductive reasoning.